2017
DOI: 10.4054/demres.2017.36.50
|View full text |Cite
|
Sign up to set email alerts
|

Divorce and separation in the Philippines: Trends and correlates

Abstract: BACKGROUNDThe Philippines is the only country in the world, aside from the Vatican, where divorce is not legal. Despite the lack of divorce law in the country and the high costs of obtaining an annulment, recent data shows that a growing number of Filipinos dissolve their marital unions, either legally or informally. OBJECTIVESI document the rise of union dissolution cases in the Philippines, and investigate the different factors associated with Filipino women's experience of union dissolution. METHODS Data i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 57 publications
1
10
0
2
Order By: Relevance
“…The study showed that urban women had higher odds of divorce compared to their rural counterparts. This finding in line with other studies [8,41,42]. The reason for this might be the difference in housing ownership and cost conflict between urban and rural couples.…”
Section: Plos Onesupporting
confidence: 92%
“…The study showed that urban women had higher odds of divorce compared to their rural counterparts. This finding in line with other studies [8,41,42]. The reason for this might be the difference in housing ownership and cost conflict between urban and rural couples.…”
Section: Plos Onesupporting
confidence: 92%
“…It appears to be among the most important predictors of marital stability, independent of the historical period (Thornton and Rodgers 1987;Martin and Bumpass 1989;Lampard 2013). A higher age at marriage is clearly associated with higher marital quality, as factors such as the partners' maturity, vulnerability to rapid changes during (late) adolescence, competence to take on marital roles, partner search time, and financial resources vary depending on their age at marriage, and should influence the quality of their marital interactions and satisfaction levels (Amato et al 2003;Abalos 2017).…”
Section: Marital Quality and Its Predictorsmentioning
confidence: 99%
“…2 части XV Конституции Филиппин 28 . Существует процедура признания брака недействительным, но это очень длительная и дорогостоящая процедура 29 .…”
Section: Abstract: Philippines Catholicism Protestantism Pentecostali...unclassified